2016
DOI: 10.1186/s12974-015-0467-5
|View full text |Cite
|
Sign up to set email alerts
|

Non-alcoholic fatty liver disease induces signs of Alzheimer’s disease (AD) in wild-type mice and accelerates pathological signs of AD in an AD model

Abstract: BackgroundNon-alcoholic fatty liver disease (NAFLD) is a chronic liver disease afflicting about one third of the world’s population and 30 % of the US population. It is induced by consumption of high-lipid diets and is characterized by liver inflammation and subsequent liver pathology. Obesity and consumption of a high-fat diet are known to increase the risk of Alzheimer’s disease (AD). Here, we investigated NAFLD-induced liver inflammation in the pathogenesis of AD.MethodsWT and APP-Tg mice were fed with a st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
225
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(261 citation statements)
references
References 56 publications
25
225
0
1
Order By: Relevance
“…ApoE deficiency significantly induced oxidative stress and inflammation in the hippocampus and cortex based on mRNA levels of related genes. Our previous analyses demonstrated that serum cholesterol levels are significantly correlated with systemic inflammation [18], which has a significant effect on the induction of neurodegeneration [4,38]. Therefore, in addition to increased expression of cytokines in the brain per se, systemic inflammation observed in hypercholesterolemic mice would aggravate the neuroinflammation in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…ApoE deficiency significantly induced oxidative stress and inflammation in the hippocampus and cortex based on mRNA levels of related genes. Our previous analyses demonstrated that serum cholesterol levels are significantly correlated with systemic inflammation [18], which has a significant effect on the induction of neurodegeneration [4,38]. Therefore, in addition to increased expression of cytokines in the brain per se, systemic inflammation observed in hypercholesterolemic mice would aggravate the neuroinflammation in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…A T-cut spinal cord hemisection injury was performed as previously described (Boato et al., 2010, Dooley et al., 2016, Geurts et al., 2015, Nelissen et al., 2013, Vangansewinkel et al., 2016, Vidal et al., 2013). See Supplemental Experimental Procedures for further details.…”
Section: Methodsmentioning
confidence: 99%
“…Spinal cord cryosections (10 μm) were obtained from animals transcardially perfused 4 weeks post injury with Ringer solution containing heparin, followed by 4% paraformaldehyde in 0.1 M PBS, and immunofluorescence analysis was performed as previously described (Boato et al., 2010, Dooley et al., 2016, Geurts et al., 2015, Nelissen et al., 2013, Vangansewinkel et al., 2016). See Supplemental Experimental Procedures for further details.…”
Section: Methodsmentioning
confidence: 99%
“…Presence of OTRs on human immune cells suggests that OT plays a role in the neuroendocrine regulation of immunity with mainly anti-inflammatory effects (Wang et al, 2015). For example, administration of OT significantly attenuates lipopolysaccharide-induced production of pro-inflammatory cytokines tumor necrosis factor alpha ( TNF-α) and interleukin 6 ( IL-6) in serum of healthy human subjects (Clodi et al, 2008) and microglial production of TNF-α and interleukin 1 beta (IL-1β) in mice (Yuan et al, 2016). Considering its anti-inflammatory effects and growing evidence that inflammatory cytokines are involved in the etiology of MDD and PPD, it can be hypothesized that insufficient OT signaling may contribute to depression risk via this pathway (McQuaid et al, 2014).…”
Section: Ot and Early-life Stress (Els) – Role In Shaping Neural Cmentioning
confidence: 99%